Gingival crevicular blood: As a non-invasive screening tool for diabetes mellitus in dental clinics - Neema Shetty; Rajesh Shankarapillai; Lalit Kumar Mathur; Balaji Manohar; Aditi Mathur; Meetu Jain (Wolters Kluwer Medknow Publications, 2013)
Background: A high number of patients with periodontitis may have undiagnosed diabetes. Self-monitoring devices provide a simple method for rapid monitoring of the glucose level in the blood by utilizing a blood sample from the finger, but this method requires a needle puncture to obtain blood. It is possible that gingival crevicular blood (GCB) from routine periodontal probing may be a source of blood for glucose measurements. Aim: To establish whether GCB can be used as a non-invasive diagnostic aid in screening for diabetes mellitus during routine periodontal examination. Materials and Methods: The study involved 50 diabetics and 50 non-diabetics, with an age range of 26-66 years. Both diabetic and non-diabetic patients had moderate to severe gingivitis with at least one tooth in the maxillary anterior region showing bleeding upon probing. The Gingival Index and Oral Hygiene Index-Simplified were recorded. Blood oozing from the gingival sulcus/pocket following periodontal pocket probing was collected using a capillary tube and transferred to the test stick of a glucose self-monitoring device (Accu-Chek, Roche Diagnostic, Germany) in patients with comparable gingival and oral hygiene status. This value was compared with the peripheral fingerstick blood glucose (PFBG) value, which was obtained by pricking the finger tip at the same visit. Statistical analysis was performed using Pearson's correlation coefficient. Result: There was no statistically significant difference between the gingival crevicular blood glucose (GCBG) values and the PFBG values in both the diabetic (P = 0.129, NS) and the non-diabetic (P = 0.503, NS) groups. Karl Pearson's product-moment correlation coefficient was calculated, which showed a positive correlation between the two measurements in the diabetic (r = 0.943) as well as the non-diabetic (r = 0.926) groups. Conclusion: The results suggest that GCB can be used as a non-invasive diagnostic aid in screening for diabetes mellitus during routine periodontal examination.